Grade 10 learners' scientific reasoning skills in characterising state of matter using physics education technology (PhET) at Seotlong Circuit, Sekhukhune East District in Limpopo, South Africa - Radingwna, Tshegofatso Mike (My University, 2024)
In Grade 10, learners had difficulty in characterising the three states of matter, solid, liquid and gas. Subsequently, the change in states of matter is too abstract and the behaviour of the particles is microscopic in nature. Due to lack of relevant resources in the school where I am teaching in Sekhukhune East District, physics education technology (PhET) simulations were used to visualise the behaviour of the particles. This assisted learners to track the behaviour of the particles that was too impossible to see with the naked eye. The theory that guided this study was the scientific discovery as dual search (SDDS) which has three tenets: the search hypothesis, the search experiment and evaluating the evidence. The qualitative approach was employed under the auspices of the exploratory case study by Merriam. At the same time, Grade 10 learners (n=40) were purposively sampled. Three instruments were used to collect data such as documents, semi-structured interviews and observations. Furthermore, data were coded using axial coding to come up with a coding scheme. Inductive thematic analyses were employed and themes emerged. The results were evaluated using the literature and theoretical framework, and principal findings were generated as follows: learners were able to exhibit scientific reasoning skills by visualising the behaviour of the particles. Subsequently, through the use of PhET simulations, the behaviour of the particles that were unclear was now visualised by learners. On the one hand, it is now clear that learners exhibit, predict, analyse, interpret, evaluate and make informed inferences when learning states of matter using PhET simulations. On the other hand, they were unable to characterise the states of matter when confronted with the simultaneous use of prediction, analysis, interpretation, evaluation and making inferences. Based on the findings of the study, the following recommendations were made. First, it was suggested that the teaching and learning of states of matter should use PhET simulations to visualise microscopic properties of states of matter. Second, there should be learning intervention that will address the simultaneous achievement of scientific reasoning skills. Hence, future studies should focus on how learners can be capacitated with the necessary knowledge to exhibit scientific reasoning skills concurrently.
Thesis (M. Ed. (Science Education)) -- University of Limpopo, 2024
Keywords: Scientific reasoning skills; PhET; Change in states of matter; Behaviour of the practices; Arrangement of the particles; Temperature; Cooling curve; Heating curve and SDDS; Reasoning; Creative ability in science; Physics -- Study and teaching